BIAS PEMBERITAAN MEDIA TENTANG PEJABAT PUBLIK - - Siswanta (Master of Public Administration, Universitas Slamet Riyadi, 2017)
This paper aimed to analyze bias of online mass media regarding allegedethics violation by public officers (speaker of House Representative). Theresearch done about 1 month, mid November till mid Desember 2015. Inthat time, news about alleged ethics violation who involved the publicofficer be headline news main stream of conventional mass media andonline mass media. The case was being tranding topic about 1 month incyber media. After that periods ending, as time goes by issue settingagenda theory, mass media changed into chief region election issues. Themedia online Merdeka.com and Suarakarya.id were research object withconsiderated both media have different ideology and politics. Dataanalysis done by using tool of analysis from Pan and Kosicki whichcovered 4 structures are syntactic, script, thematic and rhetoricalstructures. The result found that reality construction which Merdeka.comdan Suarakarya.id constructed put Setya Novanto (SN) on position aspublic officer who being objected by both media as a people who didethics violation and authority of incumbency violation, as high classmakelar, as speaker of House representative had disgrace Indonesianand SN do not deserve to be role made for other officers. Because ofreporting process framing by both online media, its bring out bias of massmedia. The bias which brough out from “Papa minta saham” case moredominated of bias by selection of sources and bias by placement. Bothmedia do news capture with refering to news sources with same theirideology and politics. Both editorial do capture and placement newsunproportionally.Keywords : framing, bias, reporting, online media, reality construction.